Combined Effect of High Hydrostatic Pressure and Proteolytic Fraction P1g10 from Vasconcellea Cundinamarcensis Latex Against Botrytis Cinerea in Grape Juice - Torres-Ossandon, M (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The effect of high hydrostatic pressure (HHP) and the proteolytic fraction P1G10 from papaya latex was studied to find out whether a synergy exists in the growth inhibition of Botrytis cinerea in grape juice, contributing to the improvement of conservation techniques and extending the shelf life and quality of food products. Grape juice (GJ) diluted to 16 °Brix with a water activity (aw) of 0.980 was prepared from a concentrated GJ and used in this study. Results indicated a 92% growth inhibition of B. cinerea when exposed to 1 mg/mL of P1G10 and 250 MPa/4 min of pressure treatment. The proximate composition and antioxidant compounds present in the GJ were not significantly affected after the treatments. Eight phenolic compounds and two flavonoids in GJ were identified and quantified, with values fluctuating between 12.77 ± 0.51 and 240.40 ± 20.9 mg/L in the control sample (0.1 MPa). The phenolic compounds showed a significant decrease after the applied treatments, with the HHP sample having a content of 65.4 ± 6.9 mg GAE/100 mL GJ. In conclusion, a synergistic effect at moderate HHP of 250 MPa/4 min with the addition of P1G10 was observed, and the successful development of a stable and acceptable GJ product was possible. © 2023 by the authors.